Phenotyping variants of tumefactive demyelinating lesions according to clinical and radiological features—A case series - Boyle, Thérèse; Fernando, Suran L.; Drummond, James; Fontes, Ariadna; Parratt, John (Frontiers in Neurology, 2023)
Background Tumefactive demyelinating lesions (TDLs) are defined as lesions greater than 2 cm on MRI of the brain. They are identified in a range of demyelinating diseases including massive demyelination due to Marburg’s acute MS, Schilder’s Disease, Balo’s concentric sclerosis, and Tumefactive MS. Apart from the rare demyelinating variants which are often diagnosed histologically, there are no detailed data to phenotype TDLs. Methods We describe the clinical and radiological features of four similar patients with very large TDLs (greater than 4 cm), that are not consistent with the rare demyelinating variants and may represent a distinct phenotype. Results All patients presented with hemiplegia and apraxia. The mean age at onset was 37 years with an equal sex distribution. All patients were diagnosed with Tumefactive Demyelination based on MRI and CSF analysis, precluding the need for brain biopsy. All responded to potent immunotherapy (including high dose corticosteroids, plasma exchange, rituximab and/or cyclophosphamide). The mean lag from diagnosis to treatment was 1 day. The median EDSS at presentation was 6 and recovery to a median EDSS of 2 occurred over 6 months.